Some aspects of the taxonomy and biology of dracunculoid nematodes parasitic in fishes: a review - Moravec, Frantisek (Folia parasitologica, 2004)
The nematode superfamily Dracunculoidea includes 166 recognized species, of which 150 (90%) are parasitic in about 300 species of freshwater, brackish-water and marine fishes. Fish dracunculoids are placed in 31 genera (86% of all dracunculoid genera) belonging to eight of the nine dracunculoid families: Anguillicolidae, Daniconematidae, Guyanemidae, Lucionematidae, Micropleuridae, Philometridae, Skrjabillanidae, and Tetanonematidae; the genus Lockenloia is considered incertae sedis. Because of difficulties in studying fish dracunculoids, associated with their morphological and biological peculiarities, most species of these largely histozoic parasites are poorly known and males of the majority of species and of eight genera have not yet been discovered. It is apparent that the present classification system of dracunculoids as a whole does not reflect phylogenetic relationships and a taxonomic revision of this nematode group, based on detailed morphological (including SEM and TEM), life history and molecular studies of individual species, is quite necessary. Data on the biology of fish dracunculoids is scarce. In known cases, their life cycles involve copepods, ostracods or branchiurids as intermediate hosts and, sometimes, fish paratenic hosts are known to occur in dracunculoid species parasitizing as adults piscivorous definitive hosts. However, nothing is known about the life cycles of representatives of 20 genera. Some species of dracunculoids, particularly of philometrids, are highly pathogenic and are known as agents of serious fish diseases. During recent years, especially the importance of Philometra spp. parasitizing the gonads of many species of marine fishes has increased due in particular to the rapid development of marine aquaculture, because they may significantly decrease fish reproduction or even cause full parasitic castration. Therefore, further detailed studies on fish dracunculoids are significant not only from the theoretical viewpoint, but they may also have practical implications.
Keywords: Animals; stadia vývoje; Female; Life Cycle Stages; zvířata; mužské pohlaví; Fishes; Dracunculoidea; Male; ženské pohlaví; ryby